PENGEMBANGAN SISTEM INFORMASI DIRECT DEBIT DONOR PROGRAMME (DDDP) DENGAN PENDEKATAN INCREMENTAL LIFE CYCLE MODEL (STUDI KASUS LEMBAGA KONSERVASI LINGKUNGAN DI JAKARTA) - Suwarjono Bausir; Achmad Hindasyah; Tukiyat Tukiyat (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2021)
Direct Debit Donor Programme (DDDP) is a donation program for individuals who are interested in taking part in social activities by direct debit of donations through bank accounts or credit cards which are commonly referred to as supporters or donors. Management of a structured and integrated information system with a good database concept will support a more effective and efficient performance. This study aims to analyze and develop the DDDP information system as a solution for supporter donation data management in increasing time efficiency. Information system development is carried out in stages starting from the need for basic functions in accordance with the development stages with the Incremental model, namely Requirements, Specifications, Architecture Design, Code and Test. modeling system development using the Unified Modeling Language (UML). Data collection was carried out through observation, direct interviews with related parties, viewing documents that were related to the research being carried out and conducting literature reviews. Functional testing on the system uses the black box testing method with the test results not found any errors in the system. The result of this research is a supporter donation data management information system which is named DDDP Application System.